Sedentary behaviors and their relationship with body composition of athletes - Júdice, P. D.; Hetherington-Rauth, M.; Magalhães, J. P.; Correia, I. R.; Sardinha, L. B. (European Journal of Sport Science, 2022)
During the recovery period, athletes present high sedentary behavior (SB). In non-athletes, there is a direct relationship between SB and obesity. However, little is known about this relationship in athletes. We hypothesized that different types of SB entail different associations with body composition outcomes.